2020
DOI: 10.1007/s11250-020-02535-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the developing gut microbiota in young dairy calves—impact of colostrum microbiota and gut disturbances

Abstract: The aim of this study was to characterize the colostrum and fecal microbiota in calves and to investigate whether fecal microbiota composition was related to colostrum microbiota or factors associated with calf health. Colostrum samples were collected in buckets after hand milking of 76 calving cows from 38 smallholder dairy farms. Fecal samples were taken directly from the rectum of 76 calves at birth and at 14 days age. The bacterial community structure in colostrum and feces was analyzed by terminal restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 24 publications
0
19
1
2
Order By: Relevance
“…One of the influencing factors that was also not considered in the study presented here is the role of the gut microbiome during pathogenesis at the site of infection in the early life of an animal, and the host-microbial interactions with dietary interventions. A number of studies have analysed the effect of the microbiome composition on new-born health such as on the calf gastrointestinal tract [ 61 , 62 , 63 , 64 , 65 ]. A limitation of our meta-analysis is that the reported prevalences in the studies were not corrected for the varying levels of sensitivity and specificity of the diagnostic tests used (also referred to as apparent prevalence).…”
Section: Discussionmentioning
confidence: 99%
“…One of the influencing factors that was also not considered in the study presented here is the role of the gut microbiome during pathogenesis at the site of infection in the early life of an animal, and the host-microbial interactions with dietary interventions. A number of studies have analysed the effect of the microbiome composition on new-born health such as on the calf gastrointestinal tract [ 61 , 62 , 63 , 64 , 65 ]. A limitation of our meta-analysis is that the reported prevalences in the studies were not corrected for the varying levels of sensitivity and specificity of the diagnostic tests used (also referred to as apparent prevalence).…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas has been consistently reported to be the dominant microbe in colostrum ( 42 ) and raw milk ( 43 ). Li et al ( 44 ) concluded that Pseudomonas, Lactococcus , and Acinetobacter were the most common genera, and Hang et al ( 45 ) found that Streptococcus, Acinetobacter, Enterobacter , and Corynebacterium were the dominant microbiota. Although those studies differed from our results, it is possible that differences in experimental approaches and even environment account for most of the discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…Although those studies differed from our results, it is possible that differences in experimental approaches and even environment account for most of the discrepancies. For example, Hang et al ( 45 ) squeezed colostrum samples into a non-sterile bucket and collected them directly from the bucket after mixing. Clearly, use of a non-sterile container likely would have contaminated the samples.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, Enhydrobacter was found to be predominant in cow colostrum 20 while facultative anaerobic bacteria such as Streptococcus, Acinetobacter, Enterobacter, and Corynebacterium were observed in another work on the same animal species 74 . The presence of anaerobic and aerobic bacteria in colostrum may participate to early gut colonization 75 .…”
Section: Colostrum Composition Dynamics Across the First 72h Post-partummentioning
confidence: 99%